Positive Impact of UV Photography on Individual Sun Protection: A Swiss Feasibility Study - Tanguy Corre; Kathrine Zimmermann; Olivier Gaide; David Vernez; Jean-Luc Bulliard (Frontiers Media S.A., 2024)
ObjectivesThis study evaluates the feasibility and impact of conveying personalized sun protection message supported by a UV photograph of the face in Switzerland.Methods440 adults from 14 private and public sites associated with high sun exposure received a skin cancer prevention intervention composed of a facial UV-filtered photograph and individual counselling by a trained registered nurse. Pre-/post intervention surveys assessed sun protection of participants, their skin cancer risk and reasons for behavioural change.ResultsThe range of facial UV spots' count per individual was very broad (0-590) and mainly determined by phototype, followed by age. Three months after the intervention, 61% of participants positively changed their sun protection habit both during leisure and at work. Use of all sun protection means increased. No factor could be specifically associated to that propension for change. The individualized message was perceived as the main motivation for change.ConclusionPersonalized sun protection messages supported by a facial UV photograph led to significant favourable behavioural change in a highly sun-exposed population of adults.